Las preguntas como estrategia para la compresión de textos de física - Ascensión Macías (Revista de Enseñanza de la Física, 2016)
This work, which is a summary of the thesis of Master in the Teaching of Physics, is about the mechanisms of control of comprehension used by students when they read, the questions they ask and the level of comprehension they achieve. The study was made using the PREG model by Otero and Graesser (2001) and it refers to the questions asked by the students when they read a Physics text.